Dilemma of Prioritising Health and the Economy During COVID-19 Pandemic in Indonesia - Siti Setiati; Muhammad K Azwar (Interna Publishing, 2020)
Since the detection of the first confirmed case of coronavirus disease 2019 (COVID-19) in early March 2020, 248,852 cases have been detected in Indonesia by 21 September 2020. At least 100 doctors have died from COVID-19 nationwide. Full large-scale social restriction was a temporary measure, followed by an early transition to the new normal era during the never-ending first wave in the country. Workers in industrial, retail, transport, and tourism fields suffered a significant decrease in work. Many countries are, however, in dilemma of protecting the health of the citizens and prioritising economy. Health should be prioritised because it is an important aspect of our lives for our economy. Poor health is estimated to reduce global gross domestic product (GDP) by 15% annually through premature deaths and potential loss of productivity of the working-age citizens. Pandemics also depress economy through decrease in both supply and demand. Data from flu pandemic a century ago suggested the importance of aggressiveness and speed of intervention. Taiwan's early action led to beneficial effects on SARS-CoV-2 infection rate and economy recovery. The target of enhancement of containment measures, provision of personal protective equipments, and testing and isolation facilities should be achieved earlier and be more than the projected demand.